Kebijakan Pemerintah Kabupaten Gunung Mas Dalam Pengendalian Kerusakan Lingkungan Pertambangan Emas Skala Kecil - Roberto Adriano Lombah; Adi Jaya; Kembarawati; Eka Noor Taufik; Emmy Uthanya Antang; Zafrullah Damanik (Jurnal Penelitian UPR, 2021)
This study is to determine the policies of the Gunung Mas Regency Government regarding Small-Scale Gold Mining in Tanjung Riu Village, to know the factors that cause small-scale gold mining activities, knowing the social impacts that occur, knowing the policies of the Gunung Mas Regency Government. This research is a qualitative descriptive study using the purposive sampling technique. The research was conducted in Tanjung Riu Village, Kurun District, Gunung Mas Regency, Central Kalimantan Province, from August to September 2019. The variables observed included (1) Economic Factors, (2) Social and Cultural Factors, (3) Government policy in implementing Community Mining Areas (WPR). The results showed that the factors causing small-scale gold mining (ASGM) in Tanjung Riu Village were economic factors with a percentage of 92.7%. The social impact resulting from Small Scale Gold Mining (ASGM) activities is the circulation of illegal drugs by 64.23%. The Gunung Mas Regency government policy regarding Small-Scale Gold Mining (PESK) is granting People's Mining Permits (IPR) and managed through the Gunung Mas Perkasa Regional Company. The community obeys government regulations by not working illegally.